Una Conversación con Cafecito y Pan Dulce: Engaging with Convivencia Testimonial in Adult Educational Research - Cindy Peña; Jessica M Quintero (Adult Education Research Conference, 2024)
Convivencia Testimonial (CvT), what is it, how is it applicable in adult educational research and what are its implications? We explore this topic through a discussion via empirical research.
Keywords: Convivencia Testimonial (CvT); Chicana feminist theory; Researcher positionality; Latino Critical Race Theory